2010
DOI: 10.1007/s00439-010-0923-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of cell-free fetal RNA suggests a specific molecular phenotype in trisomy 18

Abstract: Background Trisomy 18 is a common human aneuploidy that is associated with significant perinatal mortality. Unlike the well-characterized “critical region” in trisomy 21 (21q22), there is no corresponding region on chromosome 18 associated with its pathogenesis. The high morbidity and mortality of affected individuals has limited extensive investigations. Objective To better understand the molecular mechanisms underlying the congenital anomalies observed in this condition, we investigated the in utero gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 39 publications
2
64
0
Order By: Relevance
“…3). The RNA was extracted, amplified, labeled and hybridized to either the Affymetrix U133A expression microarray (Larrabee et al 2005) or the Affymetrix GeneChip Human Genome U133 Plus 2.0 expression microarray (Slonim et al 2009;Koide et al 2011;Hui et al 2012aHui et al ,b, 2013aEdlow et al 2014;Massingham et al 2014). Despite the availability of more sophisticated expression microarrays, the U133 Plus 2.0 was chosen because of the need for compatibility with an essential downstream in silico tool, the Connectivity Map (Lamb et al 2006).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3). The RNA was extracted, amplified, labeled and hybridized to either the Affymetrix U133A expression microarray (Larrabee et al 2005) or the Affymetrix GeneChip Human Genome U133 Plus 2.0 expression microarray (Slonim et al 2009;Koide et al 2011;Hui et al 2012aHui et al ,b, 2013aEdlow et al 2014;Massingham et al 2014). Despite the availability of more sophisticated expression microarrays, the U133 Plus 2.0 was chosen because of the need for compatibility with an essential downstream in silico tool, the Connectivity Map (Lamb et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In the studies of both DS and T18, differentially regulated genes included those that are thought to be expressed specifically from the central nervous system. This finding motivated a 2012 meta-analysis to mine previously published data (Slonim et al 2009;Koide et al 2011;Hui et al 2012a) with a specific focus on neural transcripts (Hui et al 2012b). Hui et al identified the 536 genes universally present in the cffRNA of 12 of 12 euploid samples, 746 genes universally present in the cffRNA of five of five fetuses with T18, and the 1184 genes universally present in the cffRNA of seven of seven fetuses with DS.…”
Section: Genetic Disorders: Edwards Syndromementioning
confidence: 97%
See 2 more Smart Citations
“…Functional analysis of the trisomy 18 fetuses indicated abnormalities in ion transport, immunity, DNA repair and G protein signaling and dysregulation of adrenal development-associated pathways [22].…”
Section: Aneuploidiesmentioning
confidence: 99%